The Blues Brothers [videorecording (Blu-Ray)] - Landis, John, 1950-; Landis, John, 1950-; Belushi, John; Aykroyd, Dan; Aykroyd, Dan; Calloway, Cab, 1907-1994 (Universal Studios Home Entertainment, 2011)
After their release from prison, the Blues Brothers try to reunite their rhythm and blues band in order to raise money to save the orphanage where they were raised.